Report of the Irrigation and Power Team on Nagarjunasagar Project (Andhra Pradesh) - Planning Commission, Government of India (Planning Commission, Government of India, 1960)
The Members of the Team paid a number of visits to the Nagarjunasagar Project and had detailed discussions with the Chief Engineers for Canals and Dam and other officials connected with the Project. The Leader, along with the Members of the Consultative Committee, visited the Project site from 24th to 26th October, 1958. Team gave its interim recommendations on the 9th November, 1959 which were discussed by the Consultative Committee at the meeting held at Roorkee on the same day.
Committee on Plan Projects
Committee on Plan Projects, Planning Commission, Government of India
Keywords: Canal construction and engineering